2019
DOI: 10.1007/s12310-019-09349-7
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Psychological Sense of School Membership and Postcode as Predictors of Profiles of Socio-emotional Health in Primary School Children in England

Abstract: A dual approach to mental health in schools has been widely defended, where the assessment of psychological distress and the examination of strengths/well-being are two separate continua. In line with a well-being approach, school belonging has been referenced as an important indicator of mental health in children. This study explored the predictive role of school sense of belonging alongside other demographic variables (gender, main language spoken at home, and socioeconomic status of postcode) on the socio-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Socio-economic level is given by the Index of Deprivation Affecting Children (IDACI; Smith et al, 2015), which is currently considered the best estimator of socio-economic background in England, where parental income is not available (e.g. Norbury et al, 2021;Castro-Kemp et al, 2020). Data for IDACI is available for each England borough on publicly accessible datasets on the web.…”
Section: Discussionmentioning
confidence: 99%
“…Socio-economic level is given by the Index of Deprivation Affecting Children (IDACI; Smith et al, 2015), which is currently considered the best estimator of socio-economic background in England, where parental income is not available (e.g. Norbury et al, 2021;Castro-Kemp et al, 2020). Data for IDACI is available for each England borough on publicly accessible datasets on the web.…”
Section: Discussionmentioning
confidence: 99%
“…This aggregate group of school‐related psychological assets comprise the second‐order factor of ‘student covitality’ and can be measured via the Social Emotional Health Survey—Primary (SEHS‐P) (Furlong et al, 2013). Cross‐cultural research findings indicate that higher levels of student covitality predict higher levels of school engagement (Wilkins et al, 2015), sense of school belonging/membership (Castro‐Kemp et al, 2020), school satisfaction and positive experiences (Telef, 2016), self‐reported prosocial behaviour at school (Furlong et al, 2013; Wang et al, 2018) and academic achievement (Wang et al, 2018), as well as lower levels of depressive symptoms and bullying (both victimization and perpetration) (Wang et al, 2018).…”
Section: Reading Motivation and Reading Achievement In Young Elementa...mentioning
confidence: 99%
“…Many have argued that a sense of belonging is necessary for learning and academic success [7,15,16] and school belonging has been positively associated with academic success in prior work [12,14,17,18]. Other important variables like happiness and wellbeing [19][20][21] and mental health [22][23][24][25] are also associated with school belonging. A recent meta-analysis of 82 studies affirmed the importance of school belonging by demonstrating positive correlations between school belonging and academic achievement, academic engagement and effort, and positive self-perceptions as well as a negative correlation between school belonging and school leaving, even when accounting for possible publication biases [14].…”
Section: Introductionmentioning
confidence: 99%